Breaking Barriers : Toward Better Economic Opportunities for Women in Malaysia - World Bank Group (World Bank, Washington, DC, 2019)
The promotion of economic opportunities for women is one of the most promising avenues for Malaysia's future development. Closing gaps between men's and women's economic opportunities could boost Malaysia's income per capita by 26.2 percent. Against this backdrop, the report relies on a comprehensive mixed-methods approach to investigate constraints on improving women's economic opportunities. It finds that Malaysia's female labor force participation rate has risen significantly in recent years but is still low compared to other countries in ASEAN. In addition, there are wide gender gap in access to jobs that pay well and offer benefits, social protection, and career prospects. Policy directions for improving the economic opportunities for women in Malaysia should include: (1) expand the availability, quality and affordability of child and elder care to enable more women to stay in the labor market and to work in more productive jobs; (2) strengthen the protection of informal workers and the productivity of workers and business owners to harness women's full economic potential; (3) pursue planned reforms of the legal environment and strengthen the implementation, monitoring and enforcement of laws and regulations, (4) improve support for parents, in line with international legal norms and (5) address gender norms and attitudes in education and among the wider population.